Meminimasi Reject Produk Dengan Kapabilitas Proses Menggunakan Pendekatan Lean Six Sigma - Hayu Kartika; Novera Elisa Triana; Candra Setia Bakti (Universitas Mercu Buana, 2022)
The challenges for manufacturing companies are currently getting bigger, now they are not only facing competition but companies are required to be able to survive the pandemic situation that has occurred throughout the world, including Indonesia. The purpose of this study was to minimize the number of rejects and increase the sigma value of 1 Kg cans of paint in accordance with the Straight Pass Ratio Increase (SPRI) standard of 99.3% with an acceptable percentage of 0.7% Reject. The actual condition of the reject percentage of 1kg paint cans is 6.4%, this is still far from the SPRI standard. Therefore, this research will make improvements, using the Lean Six Sigma concept using the DMAIC method in the repair process stage. The results of the study, obtained 5 types of reject that occur in the production process. In this process there are 4 factors that cause rejects, namely human factors, machines, methods and materials. The sigma value before repair was 3.7 and the cumulative process capability value was 0.062, this is still far from the specification limits that consumers expect. The improvements that have been made in this research are: implementing 5S on the production floor, 5S training and dissemination of SOPs for workers and implementing 5S as a standard operating procedure. After implementing the improvements, there was a decrease in rejects of 88.6%, an increase in the sigma value of 4.5 with a reject percentage of 0.69%. These results have reached the SPRI standards set by the company